Ascaris lumbricoides Cystatin Prevents Development of Allergic Airway Inflammation in a Mouse Model - Coronado, Sandra; Zakzuk, Josefina; Regino, Ronald; Ahumada, Velky; Benedetti, Ines; Angelina, Alba; Palomares, Oscar; Caraballo, Luis (Frontiers in Immunology, 2019)
SSevere helminth infections are negatively associated to allergic diseases like asthma; therefore, the immunomodulatory properties of parasite-derived components have been analyzed, raising the possibility of their use as anti-inflammatory molecules. We evaluated the immunomodulatory properties of Ascaris lumbricoides recombinant cysteine protease inhibitor (rAl-CPI) in a mouse model of allergic airway inflammation induced by the house dust mite (HDM) Blomia tropicalis and its effects on human monocyte-derived dendritic cells (HmoDCs). The B. tropicalis sensitized/challenged mice developed extensive cellular airway inflammatory response, which was significantly reduced upon treatment with rAl-CPI prior B. tropicalis sensitization, affecting particularly the perivascular/peribronchial infiltrate cells, eosinophils/neutrophils and goblet cells. A significant decrease of Th2 cytokines, total and specific IgE antibodies was observed in rAl-CPI treated mice. The antibody response was biased to IgG, mainly IgG2a. Administration of rAl-CPI-alone and rAl-CPI before mite sensitization were associated with a significant increase of regulatory T cells (Tregs) number in spleen and elevated IL-10 levels in BAL and splenocytes culture supernatants, which was partially affected by anti-IL10 receptor use. In vitro, rAl-CPI showed a modulatory effect on HmoDCs, lowering the expression of HLA-DR and CD83, CD86 markers and inducing IL-10 and IL-6 production. This suggests an inhibition of HmoDC maturation and a possible link with the inhibition of the allergic response observed in the murine model.